TAX LITERACY AMONG NON-ACCOUNTING MARA TVET STUDENTS: A MODERATION MODEL BASED ON THE THEORY OF PLANNED BEHAVIOUR - Said, Syafiza Hanim (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Tax literacy is increasingly recognized as a critical component of financial capability for young adults, especially those entering self-employment or gig-based income structures. Despite the Malaysian Technical and Vocational Education and Training (TVET) sector’s success in producing skilled graduates, tax education remains absent in most non-accounting programmes, including MARA TVET institutions. This gap poses significant compliance risks as graduates transition into income-generating activities requiring personal tax responsibility. Anchored in the Theory of Planned Behaviour (TPB), this conceptual paper examines the relationship between a multidimensional Tax Literacy construct and Tax Compliance Readiness among non-accounting MARA TVET students. The study proposes that this relationship is directly moderated by the Perception of Tax Education, which assesses if the perceived value of training amplifies the impact of actual literacy on compliance intent. A quantitative survey of 300 students across MARA TVET institutions in Klang Valley is recommended to test two core key hypotheses. The study contributes theoretically by refining tax literacy measurement and empirically by offering a framework for developing a tax education module tailored to TVET learners. Findings are anticipated to support curriculum integration efforts and inform policymakers on strengthening tax readiness among Bumiputera youth.